The Uniqueness of the Expression of National Peculiarities in the Novel "The Days Gone Bay". - Nortoeva Ugiloy Muhammadalievna (Zien Journals, 2022)
The article examines the issue of the fundamental problem of literary translation and the reconstruction of the national identity of a literary work. Difficulties in translating the national peculiarities of the period depicted in it.
Keywords: literary translation; peculiarity; traditions of peoples; complex realities